Interregional study destination choice: application of push, pull, and mooring model / Rendy Setya Pratama ... [et al.] - Pratama, Rendy Setya; Aditya, Valentino Dimas; Putra, Ananda Raka; Hendriana, Evelyn (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
While determinants of international student choice have been much explored. Most of these studies are descriptive without examining the strength of each antecedent on student choice. Student mobility may also occur in inter-cities or provinces in countries with uneven education distribution of higher education. By considering concepts from international student mobility, this research aims to examine the influence of various push and pull factors on interregional study destination choice. This model is enriched with the cultural distance between regions as a mooring factor that might affect the acculturation process and student decisions. The survey was conducted using purposive sampling involving first-year students from outside Java Island currently studying in Yogyakarta. Data from 477 samples were analysed using PLS-SEM. This research found that all push factors, namely perceived benefits and origin image, significantly influenced the decision to study in Yogyakarta. Pull factors consisting of institution image, destination image, and social influence also had significant effects on the decision to study in Yogyakarta. However, this research failed to demonstrate the ability of cultural distance to reduce the influence of destination and institutional images on the decision to study in Yogyakarta.